Acute central nervous system (CNS) toxicity of total body irradiation (TBI) measured using neuropsychological testing of attention functions - Wenz, Frederik; Steinvorth, Sarah; Lohr, Frank; Hacke, Werner; Wannenmacher, Michael (International journal of radiation oncology, biology, physics, 1999)
Purpose: The purpose of this study was to investigate acute normal tissue damage of low irradiation doses to the healthy, adult central nervous system (CNS) using neuropsychological testing of attention functions. Methods and Materials: Neuropsychological testing (IQ, attention [modified Trail-Making Test A, Digit Symbol Test, D2 Test, Wiener Determination Machine]) was used to examine 40 patients (43 ± 10 years) before and immediately after the first fraction (1.2 Gy) of hyperfractionated total body irradiation (TBI) at the University of Heidelberg. The patients received antiemetic premedication. Test results are given as mean percentiles ± standard deviation, with 50 ± 34 being normal. Thirty-eight control patients (53 ± 15 years) were studied to quantify the influence of hospitalization, stress, and repeated testing. Results: The patients showed normal baseline test results (IQ = 101 ± 14, attention = 54 ± 28) and no decrease in test results after 1.2 Gy TBI. Attention functions improved (66 ± 25) corresponding to a practice effect of repeated testing that was seen in the control group, although alternate versions of the tests were used (IQ = 104 ± 10, attention before = 42 ± 29, attention after = 52 ± 31). Conclusion: Our data show no deterioration of neuropsychologic test results acutely after 1.2 Gy whole body exposure in adult patients without CNS disease receiving antiemetic medication.
Gesehen am: 26.02.2015